Síntese e caracterização de partículas esféricas e submicrométricas de vidro bioativo contendo prata para potencial aplicação em curativos compósitos - Amanda Maria Almeida Coco (2021)
Biomaterials have as main objective the support, repair or regeneration of an injured tissue, with an insignificant immune response. Among the most diverse applications of these materials, there is their use in assisting lesions in the epithelial tissue. In the skin, a wound is associated with the rupture of its coating continuity due to physical damage, which is often affected by microorganisms, causing septicemia processes and even the death of patients. For this use, it is desirable to formulate a material that has properties such as biocompatibility and bioactivity, encouraging local healing, and that carries an antimicrobial character. One of the possible materials with applications for this purpose is Bioactive Glass (BG), and its recent use in the soft tissue area is highlighted by its potential in the acceleration of healing processes and action as carriers of therapeutic ions. During the synthesis of BG by the sol-gel methodology, it is possible to add antibacterial agents such as silver (Ag), which effectiveness has already been extensively discussed, but we have the absence in the literature of these ions introduction in a binary composition (Si- Ag). Therefore, in the present work, a systematic study of the obtainment of spherical and submicron BG particles was carried out with the addition of different concentrations of silver ions (0, 1, 5 and 10 mol%) obtained by a simplified and fast sol-gel methodology. The ICP assays indicated the presence of Ag in the BG, and morphological analyzes of TEM, SEM and particle size (DLS) demonstrated the achievement of the binary system (SiO2-Ag2O) with spherical particles in the submicrometric scale with sizes between 119-220nm. In the TEM analyzes it was also possible to verify the formation of silver nanoparticles (AgNP), also detected by XRD analysis. The Zeta Potential indicated a surface charge close to -30mV, demonstrating the conditions of a colloidal dispersion considered stable. XPS analyzes showed the presence of Ag+ , indicating the probability of silver ions incorporation in the silicate structure in addition to its presence in the form of metallic NP. Thus, the sol-gel methodology used presents a quick and easy way to obtain submicron, spherical and mesoporous particles of binary VB (Si-Ag), with potential application as bioceramics in composite dressings.